A novel gene expressed in rat ameloblasts codes for proteins with cell binding domains - Černý, Radim; Slabý, Ivan; Hammarstrom, Lars; Wurtz, Tilmann (Journal of bone and mineral research, 1996)
Two variants of an mRNA sequence are identified that are expressed at high levels in rat ameloblasts during the formation of the enamel matrix. The sequences contain open reading frames for 407 and 324 amino acid residues, respectively. The encoded proteins, which we call amelins, are rich in proline, glycine, leucine, and alanine residues and contain the peptide domain DGEA, an integrin recognition sequence. The sequences coding for the C-terminal 305 amino acid residues, the 3' nontranslated part, and a microsatellite repeat at the nontranslated 5' region are identical in both mRNA variants. The remaining 5' regions contain 338 nucleotides unique to the long variant, 54 common nucleotides, and 46 nucleotides present only in the short variant. Eleven nucleotides have the potential to code for 5 amino acids of both proteins in different reading frames. The reading frame of the longer variant includes codons for a typical N-terminal signal peptide. The amelins are likely to be constituents of the enamel matrix and the only proteins that have so far been implicated in binding interactions between the ameloblast surface and its extracellular matrix.
Keywords: genetický kód; Ameloblasts; Cytoskeletal Proteins; vývojová regulace genové exprese; genomová knihovna; hybridizace in situ; Gene Expression Regulation, Developmental; Rats; Protein Binding; oligonukleotidové sondy; Protein Structure, Tertiary; ameloblasty; vazba proteinů; Amino Acid Sequence; Animals; sekvence nukleotidů; Base Sequence; Nerve Tissue Proteins; In Situ Hybridization; molekulární sekvence - údaje; Genetic Code; zvířata; Rats, Sprague-Dawley; Oligonucleotide Probes; Molecular Sequence Data; terciární struktura proteinů; Genomic Library; krysa rodu Rattus; sekvence aminokyselin; cytoskeletální proteiny; proteiny nervové tkáně; potkani Sprague-Dawley